The nexus between periodontics and oral pathology. Issue 1 (21st April 2017) - Rich, Alison M.; Seo, Benedict; Parachuru, Venkata; Hussaini, Haizal M.
Abstract: A wide variety of lesions may arise from the oral mucosa, fibrous connective tissue, bone and cementum of the periodontium. The commonest pathology occurs as a result of bacterial infection and is very well known to dentists and periodontists, but rarer conditions present as gingival pathology. The pathogenesis of these conditions ranges from genetic to traumatic to immunological to neoplastic, and includes benign, malignant and metastatic lesions. This paper outlines some of these conditions and describes how the periodontist and oral pathologist can work together using a framework, and how with careful consideration of the clinical features and the use of appropriate special tests, including obtaining an adequate tissue specimen, a timely and accurate diagnosis can be obtained.